Using of the AOWI efficiency evaluation technique for ranking of the regional socio-economic systems - Slavova, T. (Математичне та комп'ютерне моделювання. Серія: Фізико-математичні науки, 2008)
In this report methods of multi-criteria efficiency evaluation are developed and implemented for ranking of the socio-economic systems of the EU regions. The socio-economic ranking problem is a multi-criteria non-convex optimization problem that is solved by the implementation of a new efficiency evaluation AOWI method. В даній роботі будуються і використовуються методи багатокритеріального ранжування соціально-економічних систем в різних регіонах ЄС. Задача соціально-економічного ранжування є задачею невипуклої багатокритеріальної оптимізації, яка розв’язується запропоно- ваним методом оцінювання AOWI.